Isolated systolic hypertension: primary care practice patterns in a Nigerian high-risk subpopulation - Ono, Agbani Ejaife; Oyekigho, Erhun Wilson; Adeleke, Ojo Araoye (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Hypertension man- agement and risk prediction based on diastolic blood pressure may be of little value for older people and people with isolated systolic hyper- tension (ISH). This study investigated primary care practice patterns in ISH management in a Nigerian high-risk subpopulation. DESIGN AND SETTING: Three-year retrospective cohort review of outpatient medical records at a state primary health care facility in south- western Nigeria. METHODS: ISH was defined according to international guidelines. Treatments were graded as relatively non-aggressive, mildly aggressive and moderately aggressive. Data were collected using a data abstraction form and statistically analyzed. RESULTS: The drug/regimen choice controlled systolic blood pressure (SBP) in only 46.90% of the population after the first visit to the clinic. SBP control among treated patients was significantly inadequate. Group mean SBP was consistently > 150 mmHg in 28.13% of the patients for  six weeks after enrollment and for at least two addi- tional visits. Data analysis revealed an increasing tendency to place patients on monotherapy or “no drug treatment” with successive visits to the clinic, even in cases of uncontrolled systolic blood pressure, as well as declining prescription of moderately aggressive combination therapy. CONCLUSION: Aggressive ISH management needs to be further emphasized at primary care levels, which for many low-income patients may be the first and last orthodox port of call.